Language Policy in Indonesia - Setyabudi, Titis (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2017)
This article attempts to elucidate language policy in Indonesia from legal perspective. Indonesia has a certain language policy that governs the use of language in this country. The Act of the Republic of Indonesia Number 24 Year 2009 concerning Flag, Language, and State Symbol, and National Anthem is the basic policy that set other policies dealing with language. This policy consists of regulation on national, local, and international language. In order to implement this policy in real life, the nation still needs hard effort from many stake-holders. In addition to many obstacles, it also invites opportunities.